2020
DOI: 10.1088/1755-1315/521/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Suitability water quality parameters for seaweed culture at Muara Gembong coastal area, Bekasi District

Abstract: Seaweed is one of the vital export aquaculture commodities in West Java of Indonesia. Since 2013, seaweed production in Muara Gembong Sub-District, especially Pantai Mekar Beach and Pantai Sederhana Villages, can be produced 7.000 tons from total 10.000 seaweed culture fisheries of Bekasi District (80%) that was developed with a polyculture system. To ensure the long-term success of providing seaweed production, evaluation of suitable location is an essential step in any aquaculture operation. This study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The results showed that water quality among the culture ponds was quite varied. Data of temperature, salinity and pH were considered to be suitable for culturing Graciliaria sp., even though water clarity and dissolved oxygen was found not suitable (Mujiyanto et al 2014). Data of water clarity in all ponds were lower than the suitable range.…”
Section: Water Quallity Parametersmentioning
confidence: 67%
See 3 more Smart Citations
“…The results showed that water quality among the culture ponds was quite varied. Data of temperature, salinity and pH were considered to be suitable for culturing Graciliaria sp., even though water clarity and dissolved oxygen was found not suitable (Mujiyanto et al 2014). Data of water clarity in all ponds were lower than the suitable range.…”
Section: Water Quallity Parametersmentioning
confidence: 67%
“…The depth of each culture pond was around one meter due to dry season when the sample collection was conducted. In addition, Mujiyanto et al (2014) stated that the Muara Gembong Estuary was classified as having shallow waters. However, in regard to the existence of macrozoobenthic communities, the water quality parameters were within the acceptable range (Marpaung et al 2014;Syamsurisal 2011).…”
Section: Water Quallity Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…The industrial demand for carrageenan, specifically in the food and beverage sector, is quite high in accordance with market demand. Moreover, excessive acidity or alkalinity in the water can affect carrageenan content in seaweed (Mujiyanto et al 2020). This plant is widely cultivated in Asian, African, and Oceania countries because of the abundance and high economic value.…”
Section: Introductionmentioning
confidence: 99%